Avaliação do efeito da adição de resíduo de borracha de pneu e brita calcária na formulação de compósitos cimentíceos - Silva Junior, Francisco Alves da (2014)
Researches have shown that the introduction of rubber in concrete improves the features of its deformability, as well as contributes to environmental disposal of waste generated in the tire retreading process. Furthermore, there is a high availability of limestone within RN and CE country. Ignorance about this stone, does not allow its wide use as aggregate, leaving, this abundant supply idle. A composite of limestone gravel, with proportions of tire rubber waste which could be used as concrete would be an alternative to concrete for low applications. Therefore, this research aims to evaluate the characteristics of concrete containing limestone gravel and proportions of little aggregate replacement (sand) by tire rubber waste. To this goal, the material components of the concrete were characterized, concrete specimens with limestone gravel were made, from the dash 1.0: 2.5: 3.5, varying the water/cement ratio, and inserting a commercial plasticizer, without a proportion of residue, known as reference. From this, concrete with and without the presence of the additive in the same proportions were chosen, as well as these with the use of granite gravel, for being the most used. Selected the references, to these, replacements of little aggregate (sand) were added replaced by rubber waste from the tire retreading process, treated with 1M NaOH in proportions from 5.0 to 20.0 % by mass, cured and exposed to the semiarid environment. The results indicate the possibility of using limestone gravel in the concrete composition with workability correction using plasticizer. There was a decrease in the mechanical properties of the concrete with increments of waste rubber, but there is an improvement in toughness and deformability of the composite, which makes it interesting for the construction of non-structural concrete floors, as well as, the rubber waste delayed the hardening process, continuing to gain resistance after 28 days